THESIS WRITING: AN ART OR A SKILL OF SCHOLAR? - Shazra Munnawer (European Scientific Journal, ESJ, 2015)
A good researcher must know the art to deduce enough information related to the topic and can apply them into his overall research project. Dissertation and thesis writing is more than essay writing. Research is a real skill that must be acquired by MPhil, PhD scholar, it is not about going to the library and getting surrounded by piles of books and it's also not about sitting in front of your computer googling something. In fact, in this phase, scholars must be selective and initially confine to the list of "must read" provided by your supervisor. PhD is the most envied degree. "Dr." or PhD is a title that distinguishes scholars from others in context of research innovative level. It is an honor that makes scholars to stand out from ‘everyone’ to someone’. Students generally get enrolled in PhD with lot of enthusiasm, unwary of the many obstacles they shall be exposed to in this labyrinth. They, by and large, do fairly well in coursework this gives them the ‘false confidence’ that thesis writing is ‘no big deal’. But as they venture in this field, they many a times regret their ‘coveted’ decision. Therefore, this present paper highlight research writing related problems and suggest practices for good research report writing .Together with this present article is no (re) search article per se, though lot of ‘search’ and ‘research’ is involved in the process. This paper may be considered as a guideline for valuable research scholars based on my own experience as a research student and Dean of higher studies.